2021
DOI: 10.3390/pharmaceutics13040510
|View full text |Cite
|
Sign up to set email alerts
|

Pre-Emptive Priming of Human Skin Improves Cutaneous Scarring and Is Superior to Immediate and Delayed Topical Anti-Scarring Treatment Post-Wounding: A Double-Blind Randomised Placebo-Controlled Clinical Trial

Abstract: The concept of pre-emptive priming of skin pre-surgery offers a novel approach in optimizing cutaneous scarring outcome. We previously showed an anti-scarring topical (epigallocatechin-3-gallate (EGCG)) is effective in improving skin scarring when applied post-surgery. The objective was to deliver an active compound at the optimal time in order to maximize its impact and improve cutaneous scarring. Therefore, pre-emptive application of anti-scarring topical pre-surgery compared with post-surgery can potentiall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 64 publications
0
16
0
Order By: Relevance
“…The trial demonstrated a significant difference in ecchymosis, skin discoloration, edema, and importantly, ongoing resolution of induration and fibrous banding over many weeks. The use of a topical product to aid in invasive surgical healing resolution is a new concept; although other researchers have used the preconditioning concept pertaining to scar control, 13 this clinical validation provides exciting new avenues for exploration and an additional adjunct to surgical procedures.…”
Section: Discussionmentioning
confidence: 99%
“…The trial demonstrated a significant difference in ecchymosis, skin discoloration, edema, and importantly, ongoing resolution of induration and fibrous banding over many weeks. The use of a topical product to aid in invasive surgical healing resolution is a new concept; although other researchers have used the preconditioning concept pertaining to scar control, 13 this clinical validation provides exciting new avenues for exploration and an additional adjunct to surgical procedures.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated that, at the site of skin wounds, the concentration of reactive oxygen species (ROS) increases and antioxidant production decreases, leading to a delayed wound healing [41]. Therefore, compounds with antioxidant potential are good therapeutic agents for accelerating the wound healing process [42].…”
Section: Discussionmentioning
confidence: 99%
“…Another option to target inflammation is by way of topical therapies which have been thought to be a viable therapeutic strategy for restricting scar tissue production and enhancing the cosmetic and functional clinical outcomes resulting from skin injury ( 74 ). Our group has conducted two double-blind randomised controlled clinical trials in humans to evaluate the concept of immediate versus delayed application of a topical formulation post-surgical wounding in an excisional punch-biopsy model ( 75 ) and the concept of pre-emptive priming of the wound site compared to immediate or delayed application ( 76 ). The objective was to deliver an active compound at the optimal time post-surgically induced injury, in order to maximise its impact and improve healing.…”
Section: Pre-emptive Priming Of Skin Prior To Injurymentioning
confidence: 99%
“…The findings from the first study provoked the hypothesis that even earlier application of an active such as EGCG could have beneficial effects on the outcome of scarring. Therefore, the second double-blind randomized placebo-controlled trial used various modes of the same anti-scarring topical formulation (containing EGCG) application utilising a full-thickness excisional surgical biopsy approach to identify whether pre-emptive priming pre-surgically induced injury had a greater impact on scarring outcome compared to immediate or delayed application ( 76 ). This demonstrated that the effects were further maximised by targeting the source of inflammation earlier.…”
Section: Pre-emptive Priming Of Skin Prior To Injurymentioning
confidence: 99%